On making a big deal. Consensus and disagreement in the newspaper coverage of UN climate summits. Issue 2 (14th March 2016) - Kumpu, Ville
ABSTRACT: This article takes part in the discussion of the post-politicization of climate change by studying how consensus and disagreement were articulated in the coverage of four UN climate summits in the Finnish newspaper Helsingin Sanomat. From the perspective of discourse theory and an agonistic theory of democracy, the article argues that the hegemonic articulation of consensual politics, solving the problem of climate change, and establishing an international treaty on emission reductions to a chain of equivalence have reduced the field of disagreement to a choice between solving and not solving climate change. While such a form of hegemony represses more radical forms of political discourse, it is often considered helpful in building the consensus that is seen as a prerequisite for decisive action on climate change. This article argues that in building a durable relationship regarding climate change, political conflicts should be embraced in the name of democratic politics rather that suppressed in the name of generating and sustaining consensus.